Barriers and Opportunities for 2-Year and 4-Year STEM Degrees: Systemic Change to Support Students' Diverse Pathways - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Nearly 40 percent of the students entering 2- and 4-year postsecondary institutions indicated their intention to major in science, technology, engineering, and mathematics (STEM) in 2012. But the barriers to students realizing their ambitions are reflected in the fact that about half of those with the intention to earn a STEM bachelor's degree and more than two-thirds intending to earn a STEM associate's degree fail to earn these degrees 4 to 6 years after their initial enrollment. Many of those who do obtain a degree take longer than the advertised length of the programs, thus raising the cost of their education. Are the STEM educational pathways any less efficient than for other fields of study? How might the losses be "stemmed" and greater efficiencies realized? These questions and others are at the heart of this study. Barriers and Opportunities for 2-Year and 4-Year STEM Degrees reviews research on the roles that people, processes, and institutions play in 2-and 4-year STEM degree production. This study pays special attention to the factors that influence students' decisions to enter, stay in, or leave STEM majors—quality of instruction, grading policies, course sequences, undergraduate learning environments, student supports, co-curricular activities, students' general academic preparedness and competence in science, family background, and governmental and institutional policies that affect STEM educational pathways. Because many students do not take the traditional 4-year path to a STEM undergraduate degree, Barriers and Opportunities describes several other common pathways and also reviews what happens to those who do not complete the journey to a degree. This book describes the major changes in student demographics; how students, view, value, and utilize programs of higher education; and how institutions can adapt to support successful student outcomes. In doing so, Barriers and Opportunities questions whether definitions and characteristics of what constitutes success in STEM should change. As this book explores these issues, it identifies where further research is needed to build a system that works for all students who aspire to STEM degrees. The conclusions of this report lay out the steps that faculty, STEM departments, colleges and universities, professional societies, and others can take to improve STEM education for all students interested in a STEM degree.
Keywords: Education

Measuring the Opportunity Gap for Children from Birth to Age Eight and Understanding Barriers to Access: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Committee on Exploring the Opportunity Gap for Young Children from Birth to Age Eight is conducting a consensus study on the causes and consequences of the opportunity gap, which generally refers to the unequal or inequitable distribution of resources and opportunities on the basis of factors such as race, ethnicity, socioeconomic status, English proficiency, community wealth, geography, or familial situations. These gaps can contribute to or perpetuate inequities in well-being across groups of young children in a number of outcome domains. As part of its work, the committee held a virtual public information-gathering workshop on May 24, 2021. The purpose of the workshop was to inform the committee in its work, which will also draw on other public information-gathering sessions, peer-reviewed research, and commissioned papers from subject-matter experts, as well as the expertise of its members. This publication summarizes the presentation and discussion of the workshop.
Keywords: Behavioral and Social Sciences

Global Change Research Needs and Opportunities for 2022-2031 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. Global Change Research Needs and Opportunities for 2022-2031 advises the USGCRP on how best to meet its mandate in light of climate change impacts happening today and projected into the future. This report identifies critical climate change risks, research needed to support decision-making relevant to managing these risks, and opportunities for the USGCRP's participating agencies and other partners to advance these research priorities over the next decade.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Preventing and Treating Alzheimer's Disease and Related Dementias: Promising Research and Opportunities to Accelerate Progress: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
In response to a request from Congress, the National Institutes of Health asked the National Academies to conduct a study to assess the current state of research on Alzheimers Disease and Related Dementias (AD/ADRD) prevention and treatment, recommend research priorities, and identify strategies for overcoming barriers that impede scientific advancement. The resulting committee held a public workshop in January 2024 to explore promising areas of research that could catalyze scientific breakthroughs or accelerate the translation of discoveries into effective prevention and treatment strategies, as well as to discuss barriers to the advancement of research. The committee final report will be released in December 2024.
Keywords: Behavioral and Social Sciences; Health and Medicine

NASA's Science Activation Program: Achievements and Opportunities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Aeronautics and Space Administration (NASA) is one of the United States' leading federal science, technology, engineering, and mathematics (STEM) agencies and plays an important role in the landscape of STEM education. In 2015, NASA's Science Mission Directorate (SMD) created the Science Activation (SciAct) program to increase the overall coherence of SMD's education efforts, to support more effective, sustainable, and efficient use of SMD science discoveries for education, and to enable NASA scientists and engineers to engage more effectively and efficiently in the STEM learning environment with learners of all ages. SciAct is now transitioning into its second round of funding, and it is beneficial to review the program's portfolio and identify opportunities for improvement. NASA's Science Activation Program: Achievements and Opportunities assesses SciAct's efforts towards meeting its goals. The key objectives of SciAct are to enable STEM education, improve U.S. scientific literacy, advance national education goals, and leverage efforts through partnerships. This report describes and assesses the history, current status, and vision of the program and its projects. It also provides recommendations to enhance NASA's efforts through the SciAct program.
Keywords: Education

Measuring Law Enforcement Suicide: Challenges and Opportunities: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
From April 25-26, 2023 the Committee on National Statistics of the National Academies of Sciences, Engineering, and Medicine convened a workshop to identify challenges in and opportunities for measuring suicide in the law enforcement occupation. Experts in the field met to identify ways to improve the measurement of suicide by current and former police and corrections officers, dispatchers, and other sworn and civilian personnel, in public and private organizations. This proceedings provides a synthesis of key themes identified during the workshop.
Keywords: Behavioral and Social Sciences

Social Isolation and Loneliness in Older Adults: Opportunities for the Health Care System - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Social isolation and loneliness are serious yet underappreciated public health risks that affect a significant portion of the older adult population. Approximately one-quarter of community-dwelling Americans aged 65 and older are considered to be socially isolated, and a significant proportion of adults in the United States report feeling lonely. People who are 50 years of age or older are more likely to experience many of the risk factors that can cause or exacerbate social isolation or loneliness, such as living alone, the loss of family or friends, chronic illness, and sensory impairments. Over a life course, social isolation and loneliness may be episodic or chronic, depending upon an individual's circumstances and perceptions. A substantial body of evidence demonstrates that social isolation presents a major risk for premature mortality, comparable to other risk factors such as high blood pressure, smoking, or obesity. As older adults are particularly high-volume and high-frequency users of the health care system, there is an opportunity for health care professionals to identify, prevent, and mitigate the adverse health impacts of social isolation and loneliness in older adults. Social Isolation and Loneliness in Older Adults summarizes the evidence base and explores how social isolation and loneliness affect health and quality of life in adults aged 50 and older, particularly among low income, underserved, and vulnerable populations. This report makes recommendations specifically for clinical settings of health care to identify those who suffer the resultant negative health impacts of social isolation and loneliness and target interventions to improve their social conditions. Social Isolation and Loneliness in Older Adults considers clinical tools and methodologies, better education and training for the health care workforce, and dissemination and implementation that will be important for translating research into practice, especially as the evidence base for effective interventions continues to flourish.
Keywords: Behavioral and Social Sciences; Health and Medicine

Data Science for Undergraduates: Opportunities and Options - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Data science is emerging as a field that is revolutionizing science and industries alike. Work across nearly all domains is becoming more data driven, affecting both the jobs that are available and the skills that are required. As more data and ways of analyzing them become available, more aspects of the economy, society, and daily life will become dependent on data. It is imperative that educators, administrators, and students begin today to consider how to best prepare for and keep pace with this data-driven era of tomorrow. Undergraduate teaching, in particular, offers a critical link in offering more data science exposure to students and expanding the supply of data science talent. Data Science for Undergraduates: Opportunities and Options offers a vision for the emerging discipline of data science at the undergraduate level. This report outlines some considerations and approaches for academic institutions and others in the broader data science communities to help guide the ongoing transformation of this field.
Keywords: Computers and Information Technology; Math, Chemistry, and Physics; Education; Surveys and Statistics

Identifying Opportunities for Prevention and Intervention in the Youth Depression Cascade: Workshop in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On November 19, 2015, the Forum on Promoting Children's Cognitive, Affective, and Behavioral Health of the National Academies of Sciences, Engineering, and Medicine cohosted a webinar with the American Academy of Pediatrics on prevention and intervention methods to address the development of clinical depression in children and adolescents. The webinar featured three presentations focused on various opportunities to identify and intervene in developing cases of clinical depression within current health care settings, viewing the detection and care of depression as a series of steps that a practice could take.
Keywords: Behavioral and Social Sciences; Health and Medicine

Summertime Opportunities to Promote Healthy Child and Adolescent Development: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
What children and adolescents do and learn in the summertime can have profound effects on their health and well-being, educational attainment, and career prospects. To explore the influence of summertime activities on the lives of young people, the National Academies of Sciences, Engineering, and Medicine held a workshop in August 2016. The participants discussed a wide range of topics, including the value of play, healthy eating and physical activity, systemic approaches to skill development, program quality and measurement, and the interconnected ecosystem of activities that supports healthy development. The workshop highlighted the latest research on summer programming, as well as gaps in that research, and explored the key policy and practice issues for summertime opportunities to promote healthy child and adolescent development. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences

Opportunities to Promote Children's Behavioral Health: Health Care Reform and Beyond: Workshop in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The adoption of the Patient Protection and Affordable Care Act (ACA) 2010 was a turning point in the history of behavioral health for children and adolescents in the United States. The ACA requires most health insurance plans to conduct behavioral health assessments for children, as well as depression screening for adults. Looking ahead, however, questions have been raised about how to promote children's behavioral health, how to make use of innovations, and how to sustain funding over time. To respond to these questions, the Forum on Promoting Children's Cognitive, Affective, and Behavioral Health of the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, D.C., on April 1-2, 2015. The workshop focused on how recent reforms in health care provide new opportunities to promote children's cognitive, affective, and behavioral health. It also assessed behavioral health needs of all children, including those with special physical or behavioral health conditions, and programs that support families.This report summarizes the presentations and discussion of the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Exploring Opportunities for STEM Teacher Leadership: Summary of a Convocation - National Research Council (The National Academies Press, 2014)
Many national initiatives in K-12 science, technology, engineering, and mathematics (STEM) education have emphasized the connections between teachers and improved student learning. Much of the discussion surrounding these initiatives has focused on the preparation, professional development, evaluation, compensation, and career advancement of teachers. Yet one critical set of voices has been largely missing from this discussion - that of classroom teachers themselves. To explore the potential for STEM teacher leaders to improve student learning through involvement in education policy and decision making, the National Research Council held a convocation in June 2014 entitled "One Year After Science's Grand Challenges in Education: Professional Leadership of STEM Teachers through Education Policy and Decision Making". This event was structured around a special issue of Science magazine that discussed 20 grand challenges in science education. The authors of three major articles in that issue - along with Dr. Bruce Alberts, Science's editor-in-chief at the time - spoke at the convocation, updating their earlier observations and applying them directly to the issue of STEM teacher leadership. The convocation focused on empowering teachers to play greater leadership roles in education policy and decision making in STEM education at the national, state, and local levels. Exploring Opportunities for STEM Teacher Leadership is a record of the presentations and discussion of that event. This report will be of interest to STEM teachers, education professionals, and state and local policy makers.
Keywords: Education

Learning Through Citizen Science: Enhancing Opportunities by Design - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
In the last twenty years, citizen science has blossomed as a way to engage a broad range of individuals in doing science. Citizen science projects focus on, but are not limited to, nonscientists participating in the processes of scientific research, with the intended goal of advancing and using scientific knowledge. A rich range of projects extend this focus in myriad directions, and the boundaries of citizen science as a field are not clearly delineated. Citizen science involves a growing community of professional practitioners, participants, and stakeholders, and a thriving collection of projects. While citizen science is often recognized for its potential to engage the public in science, it is also uniquely positioned to support and extend participants' learning in science. Contemporary understandings of science learning continue to advance. Indeed, modern theories of learning recognize that science learning is complex and multifaceted. Learning is affected by factors that are individual, social, cultural, and institutional, and learning occurs in virtually any context and at every age. Current understandings of science learning also suggest that science learning extends well beyond content knowledge in a domain to include understanding of the nature and methods of science. Learning Through Citizen Science: Enhancing Opportunities by Design discusses the potential of citizen science to support science learning and identifies promising practices and programs that exemplify the promising practices. This report also lays out a research agenda that can fill gaps in the current understanding of how citizen science can support science learning and enhance science education.
Keywords: Education

Science Teachers' Learning: Enhancing Opportunities, Creating Supportive Contexts - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
Currently, many states are adopting the Next Generation Science Standards (NGSS) or are revising their own state standards in ways that reflect the NGSS. For students and schools, the implementation of any science standards rests with teachers. For those teachers, an evolving understanding about how best to teach science represents a significant transition in the way science is currently taught in most classrooms and it will require most science teachers to change how they teach. That change will require learning opportunities for teachers that reinforce and expand their knowledge of the major ideas and concepts in science, their familiarity with a range of instructional strategies, and the skills to implement those strategies in the classroom. Providing these kinds of learning opportunities in turn will require profound changes to current approaches to supporting teachers' learning across their careers, from their initial training to continuing professional development. A teacher's capability to improve students' scientific understanding is heavily influenced by the school and district in which they work, the community in which the school is located, and the larger professional communities to which they belong. Science Teachers' Learning provides guidance for schools and districts on how best to support teachers' learning and how to implement successful programs for professional development. This report makes actionable recommendations for science teachers' learning that take a broad view of what is known about science education, how and when teachers learn, and education policies that directly and indirectly shape what teachers are able to learn and teach. The challenge of developing the expertise teachers need to implement the NGSS presents an opportunity to rethink professional learning for science teachers. Science Teachers' Learning will be a valuable resource for classrooms, departments, schools, districts, and professional organizations as they move to new ways to teach science.
Keywords: Education

Measuring Access to Learning Opportunities - National Research Council (The National Academies Press, 2003)
Since 1968 the Elementary and Secondary School Civil Rights Compliance Report (known as the E&S survey) has been used to gather information about possible disparities in access to learning opportunities and violations of students’ civil rights. Thirty-five years after the initiation of the E&S survey, large disparities remain both in educational outcomes and in access to learning opportunities and resources. These disparities may reflect violations of students’ civil rights, the failure of education policies and practices to provide students from all backgrounds with a similar educational experience, or both. They may also reflect the failure of schools to fully compensate for disparities and current differences in parents’ education, income, and family structure. The Committee on Improving Measures of Access to Equal Educational Opportunities concludes that the E&S survey continues to play an essential role in documenting these disparities and in providing information that is useful both in guiding efforts to protect students’ civil rights and for informing educational policy and practice. The committee also concludes that the survey’s usefulness and access to the survey data could be improved.
Keywords: Education; Behavioral and Social Sciences; Surveys and Statistics

Realizing the Potential of the American Community Survey: Challenges, Tradeoffs, and Opportunities - National Research Council (The National Academies Press, 2015)
The American Community Survey (ACS) was conceptualized as a replacement to the census long form, which collected detailed population and housing data from a sample of the U.S. population, once a decade, as part of the decennial census operations. The long form was traditionally the main source of socio-economic information for areas below the national level. The data provided for small areas, such as counties, municipalities, and neighborhoods is what made the long form unique, and what makes the ACS unique today. Since the successful transition from the decennial long form in 2005, the ACS has become an invaluable resource for many stakeholders, particularly for meeting national and state level data needs. However, due to inadequate sample sizes, a major challenge for the survey is producing reliable estimates for smaller geographic areas, which is a concern because of the unique role fulfilled by the long form, and now the ACS, of providing data with a geographic granularity that no other federal survey could provide. In addition to the primary challenge associated with the reliability of the estimates, this is also a good time to assess other aspects of the survey in order to identify opportunities for refinement based on the experience of the first few years. Realizing the Potential of the American Community Survey provides input on ways of improving the ACS, focusing on two priority areas: identifying methods that could improve the quality of the data available for small areas, and suggesting changes that would increase the survey's efficiency in responding to new data needs. This report considers changes that the ACS office should consider over the course of the next few years in order to further improve the ACS data. The recommendations of Realizing the Potential of the American Community Survey will help the Census Bureau improve performance in several areas, which may ultimately lead to improved data products as the survey enters its next decade.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

The Aging Mind: Opportunities in Cognitive Research - National Research Council (The National Academies Press, 2000)
Possible new breakthroughs in understanding the aging mind that can be used to benefit older people are now emerging from research. This volume identifies the key scientific advances and the opportunities they bring. For example, science has learned that among older adults who do not suffer from Alzheimer's disease or other dementias, cognitive decline may depend less on loss of brain cells than on changes in the health of neurons and neural networks. Research on the processes that maintain neural health shows promise of revealing new ways to promote cognitive functioning in older people. Research is also showing how cognitive functioning depends on the conjunction of biology and culture. The ways older people adapt to changes in their nervous systems, and perhaps the changes themselves, are shaped by past life experiences, present living situations, changing motives, cultural expectations, and emerging technology, as well as by their physical health status and sensory-motor capabilities. Improved understanding of how physical and contextual factors interact can help explain why some cognitive functions are impaired in aging while others are spared and why cognitive capability is impaired in some older adults and spared in others. On the basis of these exciting findings, the report makes specific recommends that the U.S. government support three major new initiatives as the next steps for research.
Keywords: Behavioral and Social Sciences; Health and Medicine

Research Opportunities Concerning the Causes and Consequences of Child Food Insecurity and Hunger: Workshop Summary - National Research Council; Institute of Medicine (The National Academies Press, 2013)
Section 141 of The Healthy, Hunger-Free Kids Act of 20101 provides funding for a research program on the causes and consequences of childhood hunger and food insecurity, and the characteristics of households with childhood hunger and food insecurity, with a particular focus on efforts to improve the knowledge base regarding contributing factors, geographic distribution, programmatic effectiveness, public health and medical costs, and consequences for child development, well-being, and educational attainment. The Economic Research Service and Food and Nutrition Service of the US Department of Agriculture conducted two outreach efforts to obtain input from the research community and other stakeholders to help focus on areas and methods with the greatest research potential. First, Food and Nutrition Service sought written comments to selected questions through publication of a Federal Register Notice. The second option was to convene a workshop under the auspices of the Committee on National Statistics of the National Research Council and the Food and Nutrition Board of the Institute of Medicine. Research Opportunities Concerning the Causes and Consequences of Child Food Insecurity and Hunger is the summary of that workshop, convened in Fall 2012 to examine research gaps and opportunities to advance understanding of the causes and consequences of child hunger in the United States. This report reviews the adequacy of current knowledge, identifies substantial research gaps, and considers data availability of economic, health, social, cultural, demographic, and other factors that contribute to childhood hunger or food insecurity. It also considers the geographic distribution of childhood hunger and food insecurity; the extent to which existing federal assistance programs reduce childhood hunger and food insecurity; childhood hunger and food insecurity persistence, and the extent to which it is due to gaps in program coverage; and the inability of potential participants to access programs, or the insufficiency of program benefits or services. Research Opportunities Concerning the Causes and Consequences of Child Food Insecurity and Hunger will be a resource to inform discussions about the public health and medical costs of childhood hunger and food insecurity through its focus on determinants of child food insecurity and hunger, individual, community, and policy responses to hunger, impacts of child food insecurity and hunger, and measurement and surveillance issues.
Keywords: Food and Nutrition; Behavioral and Social Sciences; Health and Medicine

Undergraduate Research Experiences for STEM Students: Successes, Challenges, and Opportunities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Undergraduate research has a rich history, and many practicing researchers point to undergraduate research experiences (UREs) as crucial to their own career success. There are many ongoing efforts to improve undergraduate science, technology, engineering, and mathematics (STEM) education that focus on increasing the active engagement of students and decreasing traditional lecture-based teaching, and UREs have been proposed as a solution to these efforts and may be a key strategy for broadening participation in STEM. In light of the proposals questions have been asked about what is known about student participation in UREs, best practices in UREs design, and evidence of beneficial outcomes from UREs. Undergraduate Research Experiences for STEM Students provides a comprehensive overview of and insights about the current and rapidly evolving types of UREs, in an effort to improve understanding of the complexity of UREs in terms of their content, their surrounding context, the diversity of the student participants, and the opportunities for learning provided by a research experience. This study analyzes UREs by considering them as part of a learning system that is shaped by forces related to national policy, institutional leadership, and departmental culture, as well as by the interactions among faculty, other mentors, and students. The report provides a set of questions to be considered by those implementing UREs as well as an agenda for future research that can help answer questions about how UREs work and which aspects of the experiences are most powerful.
Keywords: Education

The Early Childhood Care and Education Workforce: Challenges and Opportunities: A Workshop Report - Institute of Medicine; National Research Council (The National Academies Press, 2012)
Early childhood care and education (ECCE) settings offer an opportunity to provide children with a solid beginning in all areas of their development. The quality and efficacy of these settings depend largely on the individuals within the ECCE workforce. Policy makers need a complete picture of ECCE teachers and caregivers in order to tackle the persistent challenges facing this workforce. The IOM and the National Research Council hosted a workshop to describe the ECCE workforce and outline its parameters. Speakers explored issues in defining and describing the workforce, the marketplace of ECCE, the effects of the workforce on children, the contextual factors that shape the workforce, and opportunities for strengthening ECCE as a profession.
Keywords: Health and Medicine; Behavioral and Social Sciences